Pipistrellus kuhlii - Don E. Wilson; Russell A. Mittermeier (Lynx Edicions, 2019)
24. Kuhl’s Pipistrelle Pipistrellus kuhlii French: Pipistrelle de Kuhl / German: WeiRrandfledermaus / Spanish: Pipistrela de borde claro Other common names: Kuhl's Bat, Kuhl’s Pipistrelle Bat, Great Pipistrelle, White Stripe Bat Taxonomy. Vespertilio kuhlii Natterer in Kuhl, 1817, Trieste, Italy. Pipistrellus desert: Thomas, 1902 was recognized as a synonym by O. Thomas in 1902, and individuals from sub-Saharan Africa are considered to belong to P. hesperidus. Nevertheless, phylogenetic relationships among these taxa need additional research. Populations of P. kuhlii in the Canary Islands might also represent P. hesperidus, and are tentatively included underlatter species here. Although P. maderensis is currently considered a distinct species, genetic data have shown that it is imbedded in P. kuhlii. This suggests that either P. maderensis is best included under P. kuhlii or P. kuhlii represents multiple species. Four subspecies recognized. Subspecies and Distribution. P.k.kuhliiNatterer,1817—C&SEurope,fromNFranceandIberianPeninsulaEtotheBalkans,limitinginNinSGermany,SCzechRepublic,Austria,andSlovakia;alsoonlargeMediterraneanIs. P.k.tkhwaniusCheesman&Hinton,1924—EAsiainSyria,Lebanon,Israel,Jordan,Iraq,Iran,andArabianPeninsula. P.k.lepidusBlyth,1845—SPoland,extremeESlovakia,Romania,Ukraine,WRussia,WKazakhstan,Caucasus,Anatolia,Uzbekistan,Turkmenistan,Afghanistan,Pakistan,andIndia. P. k. marginatus Cretzschmar, 1830 — N Africa from Morocco E to Egypt. Descriptive notes. Head-body 40-55 mm, tail 30-45 mm, ear 12-13 mm, hindfoot 6-8 mm, forearm 30-3-37-4 mm; weight 5-10 g. Kuhl’s Pipistrelle has very variable fur color from dark to pale brown, rusty brown, or yellowish, with no sexual dimorphism. Contrast between dorsum and venter is not very clear, and although dorsal hair is often beige to ocher, ventral hair tends to be whitish or pale yellowish. Skin varies from dark brown to pale or reddish. Commonly, white stripe of different widths can be found at free edge of wing and tail membranes. In eastern ...